Common variable immunodeficiency (CVID) presenting with malabsorption due to giardiasis - Kevser ONBAŞI; Fulya GÜNŞAR; Aytül Z. SİN and Ömür ARDENİZ and Ali KOKULUDAĞ and Filiz SEBİK (Turkish Journal of Gastroenterology, 2019)
-